Complications associated with transtoracic biopsies - Costa, Ana (2020)
Transthoracic Biopsy is a complementary diagnostic test used to diagnose lung, pleural and mediastinal injuries. This procedure, performed through puncture with intermittent support of axial images, or with Fluro-CT, in which the control of the needle position is done in real time, according to a minimally invasive method, can be performed in an outpatient setting. The type and size of the needle to be selected is done according to the type of biopsy to be performed (cytology or histology). This means of diagnosis can be influenced by factors inherent to the patient, experience of the executing physician, type of needle, etc. The objective of this project is to analyze the complications of transthoracic biopsies in patients enrolled at the Portuguese Institute of Oncology in Oporto and who will be subjected to this procedure, in order to clarify and establish the reality of the Radiology Intervention Service.